Tuberculous and Nontuberculous Cervical Lymphadenitis: A Clinical Review - Shrestha, D; Thapa, P; Dahal, M (Nepalese Journal of ENT Head and Neck Surgery, 2011)
Keywords: Tubercular cervixal lymphadenitis; fine needle aspiration cytology; biopsy; histopathological examiniation DOI: 10.3126/njenthns.v1i2.4757 Nepalese J ENT Head Neck Surg Vol.1 No.2 (2010) p.12-13